2021
DOI: 10.1080/07853890.2020.1853215
|View full text |Cite
|
Sign up to set email alerts
|

Childhood exposure to parental smoking and life-course overweight and central obesity

Abstract: Objective To evaluate the association between childhood parental smoking exposure and the risk of overweight/obesity from childhood to adulthood. Methods This study leverages the data from two longitudinal population based cohort studies, the Cardiovascular Risk in Young Finns Study between years 1980–2011/2012 (YFS; N = 2,303; baseline age 3–18 years) and the Special Turku Coronary Risk Factor Intervention Project between years 1989–2009/2010… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 40 publications
1
11
0
Order By: Relevance
“…Individuals in the 'very high risk' group had fewer mothers that had never smoked or were former smokers. Childhood parental smoking exposure was previously associated with increased risk for life-course overweight or obesity and/or abdominal obesity [47,53].…”
Section: Discussionmentioning
confidence: 99%
“…Individuals in the 'very high risk' group had fewer mothers that had never smoked or were former smokers. Childhood parental smoking exposure was previously associated with increased risk for life-course overweight or obesity and/or abdominal obesity [47,53].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study indicated that childhood exposure to parental smoking was associated with an increased risk of overweight and abdominal obesity. 23 Another study showed that obesity was highly related to tobacco smoking. 24 Active and passive smoking are typically accompanied by increased weight, and smokers tend to be either obese or overweight.…”
Section: Discussionmentioning
confidence: 99%
“…Possible common early life exposure candidates, which are risk factors for both asthma and obesity, include maternal BMI, 32,33 early antibiotic use, 34 mode of delivery, 34 early feeding practices, 35 poverty and environmental smoke. 36,37 High birth weight in early childhood is associated with both asthma and obesity suggesting a role of early BMI on later outcomes. 38 Additionally, catch-up growth, a period of faster weight gain during the first 2 years of life, has been associated with the risk of obesity 39 and asthma separately.…”
Section: Asthma and Obesitymentioning
confidence: 99%